2020
DOI: 10.1038/s41467-020-18178-1
|View full text |Cite
|
Sign up to set email alerts
|

Serological identification of SARS-CoV-2 infections among children visiting a hospital during the initial Seattle outbreak

Abstract: Children are strikingly underrepresented in COVID-19 case counts. In the United States, children represent 22% of the population but only 1.7% of confirmed SARS-CoV-2 cases as of April 2, 2020. One possibility is that symptom-based viral testing is less likely to identify infected children, since they often experience milder disease than adults. Here, to better assess the frequency of pediatric SARS-CoV-2 infection, we serologically screen 1,775 residual samples from Seattle Children's Hospital collected from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 42 publications
4
67
2
Order By: Relevance
“…One study has shown that children are less likely to develop symptomatic infection, with the probability of having clinically meaningful COVID-19 dropping from approximately 70% in older adults to approximately 20% in children [ 17 ]. Furthermore, in a study of 1775 residual samples collected in 1076 children requesting medical attention at Seattle Children's Hospital, a seroprevalence of ≈1% was reported [ 18 ]. In a Dutch cohort of 3207 citizens aged 2–90 years, seroprevalance estimates were 4.9% in the 18–39 year age group compared with 1.7% in children 2–17 years of age [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study has shown that children are less likely to develop symptomatic infection, with the probability of having clinically meaningful COVID-19 dropping from approximately 70% in older adults to approximately 20% in children [ 17 ]. Furthermore, in a study of 1775 residual samples collected in 1076 children requesting medical attention at Seattle Children's Hospital, a seroprevalence of ≈1% was reported [ 18 ]. In a Dutch cohort of 3207 citizens aged 2–90 years, seroprevalance estimates were 4.9% in the 18–39 year age group compared with 1.7% in children 2–17 years of age [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…• Two studies found children generally developed a detectable antibody response to SARS-CoV-2 infection [99,100]. • Two studies found children with pneumonia generally mounted lower IgG [101] and IgA responses [102].…”
Section: Childrenmentioning
confidence: 99%
“…Neutralising antibody kinetics. Across the included studies, the majority of subjects developed detectable neutralising antibodies in response to SARS-CoV-2 infection in both human [7,18,22,29,76,100, and animal [41,[128][129][130][131] participants. However, neutralising antibody titres were low in a substantial minority of participants.…”
Section: Protective Immunitymentioning
confidence: 99%
“…Several studies have described the general adaptive immune responses towards SARS-CoV-2, showing that SARS-CoV-2 specific B and T cells are generated during infections. First immunoglobulin (Ig) M and later IgG SARS-CoV-2 spike specific antibodies are readily detected in COVID-19 patients [8][9][10][11][12]. Evaluations by neutralization assays have confirmed the ability of the generated antibodies to prevent viral infections in vitro [13][14][15].…”
Section: Introductionmentioning
confidence: 96%